Who is the author of this Editorial? - Angervall, Petra (Journal of Praxis in Higher Education, 2025)
Since the journal’s launch in 2018, the Editorial in each issue has been an important space for our team to voice ideas, concerns, and interests, as well as to introduce the new issue. We have used the Editorial to articulate our mission and nurture a shared sense of collective identity. I believe we take genuine pleasure in writing these pieces - their varied images and reflections - and the team shares the responsibility for creating them.